PTU-182 Can response to pharyngeal stimulation in dysphagic stroke be predicted by bdnf genetic polymorphisms?. (22nd June 2015) - Essa, H; Vasant, D; Raginis-Zborowska, A; Payton, A; Michou, E; Hamdy, S
Abstract : Introduction: Pharyngeal electrical stimulation (PES) has shown promise as a novel treatment option for dysphagia after stroke. Furthermore, we have shown that the BDNF Val66Met polymorphism is strongly associated with cortical plasticity to neurostimulation in the pharyngeal motor system (Gastroenterology 2011;141:827–836). However, the ability to predict response outcome and the factors associated with stimulation driven dysphagia recovery are unclear. This study aims to elucidate the role of common genetic polymorphisms in influencing response to PES. Method: 38 dysphagic stroke patients were recruited for a single blinded randomised control trial of active or sham PES over a 4 year period. Swallowing outcome was assessed by a validated dysphagia severity rating scale, recorded at baseline, 2 weeks and 3 months post recruitment. Saliva samples were obtained during the recruitment phase for DNA extraction and genotyped for the BDNF polymorphism Val66Met rs76265. Response to PES was correlated with BDNF status. Statistical analysis was performed using a linear regression model adjusting for stroke severity (based on NIHSS score) and patient's age. Results: Of the 38 patients recruited, 20 patients provided quantifiable saliva samples, of which 16 (8 in the active group and 8 in the sham group) were clean enough for DNA extraction. Analysis revealed that in the active stimulation group the presence of the BDNF Met allele demonstrated significantly greater improvements at the 3 months stage as compared to non-Met allele counterparts (F(2, 4) 23.89, p = . 009). No associations were seen in the sham group. Conclusion: This novel study has found intriguing associations between BDNF polymorphisms and stimulation related swallowing recovery that warrant further research. Disclosure of interest: H. Essa: None Declared, D. Vasant: None Declared, A. Raginis-Zborowska: None Declared, A. Payton: None Declared, E. Michou: None Declared, S. Hamdy Conflict with: Provide scientific advice to Phagenesis Ltd.